Never say die : would they have what it takes to make it out alive - McCollum, Sean (Scholastic Inc., 2012)
Trapped in a lonely Utah canyon, Aron Ralston was forced to confront the unthinkable in order to make it out alive. Left for dead on an icy mountain in Peru, Joe Simpson faced a choice: drag himself to camp on a shattered knee or die alone 4000 miles from home.